Novel Nitinol Stent for Lesions up to 24 cm in the Superficial Femoral and Proximal Popliteal Arteries: 24-Month Results From the TIGRIS Randomized Trial. (February 2018) - Laird, John R.; Zeller, Thomas; Loewe, Christian; Chamberlin, Jack; Begg, Richard; Schneider, Peter A.; Nanjundappa, Aravinda; Bunch, Frank; Schultz, Scott; Harlin, Stuart; Lansky, Alexandra; Jaff, Michael R.
Purpose: To evaluate the safety and effectiveness of the TIGRIS stent for lesions up to 24 cm in the superficial femoral and proximal popliteal arteries (SFA/PPA).Methods: This prospective, multicenter, randomized study enrolled 274 subjects at 36 sites in the United States and Europe. Subjects were randomly assigned in a 3:1 ratio to treatment with the TIGRIS stent (n=197; mean age 66.7±9.28 years; 141 men) or LifeStent (n=70; mean age 67.9±8.87 years; 49 men). The primary safety endpoint was 30-day freedom from major adverse events (MAE). The primary efficacy endpoint was primary patency at 12 months. Secondary endpoints included target lesion revascularization (TLR) and stent fracture. Clinical success and quality of life were also assessed.Results: Mean lesion length (107.6 vs 117.9 mm, p=0.29), procedure success (99.5% vs 97.1%, p=0.17), and freedom from MAE (99.5% vs 100%, p>0.99) were similar for the TIGRIS and control groups, respectively. Likewise, there was no difference in primary patency at 12 months (60.6% vs 63.2%, p=0.73) or 24 months (56.3% vs 50.2%, p=0.60) or in TLR at the same time points (76.6% vs 80.6%, p=0.49; 70.5% vs 67.2%, p=0.85). There were no differences in the changes in Rutherford category or the ankle/brachial index through 24 months. The rate of stent fracture was lower for TIGRIS compared with LifeStent (0% vs 32.7%, p<0.001).Conclusion: The TIGRIS stent and LifeStent were similarly effective for the treatment of lesions in the SFA and PPA. The high flexibility and zero fracture rate associated with the TIGRIS stent make this device favorable for use in high-flexion arteries.